The EU as catalytic state? Rethinking European climate and energy governance. Issue 3 (4th May 2022) - Prontera, Andrea; Quitzow, Rainer
ABSTRACT: The regulatory state has provided a useful framework for conceptualizing the nature of the EU and its role in policy making. Although it is widely accepted that the conditions of European integration have dramatically changed since the 1990s, when this approach was formulated, few scholars have sought to theorize the EU 'beyond' the regulatory state. To fill this gap, this article puts forward the concept of the catalytic state, tracing its emergence within the field of climate and energy. The article proposes an initial theorization of the EU's role as a catalytic state, situating it between the direct approach of the positive state and the indirect one of the regulatory state. On that basis, it provides a detailed mapping of catalytic state capacities in the climate and energy sector. Rather than replacing existing regulatory capacities, the paper argues, these new capacities have expanded the scope of EU action, following the logic of policy layering. To what extent this has indeed increased the ability of the EU to achieve its declared policy targets remains an open question, however. The paper concludes with a discussion of further research questions regarding the effectiveness, accountability and scope of the EU as a catalytic state.